Regulation of production of delta-aminolaevulinate synthase in tissues of chick embryos. Effects of porphyrogenic agents and of haem precursors. - Drew, P D (1989)
Studies conducted by several groups have established that porphyrogenic agents which caused elevations in chick-embryo liver delta-aminolaevulinate (ALA) synthase activity also increased the concentrations of the enzyme's RNA, and that haemin inhibited these elevations. We have determined in this study, using immune-blot analyses, that administration in ovo of allylisopropylacetamide (AIA) in combination with diethyl 1,4-dihydro-2,4,6-trimethyl,3,5-pyridinedicarboxylate (DDC) increased the mass of ALA synthase in intestine and kidney of chick embryos. Furthermore, the molecular mass of the subunit of the enzyme in those tissues appeared identical with that of liver ALA synthase. Using a synthetic oligonucleotide complementary to ALA synthase mRNA, we determined by solution hybridization and Northern-blot analyses that AIA and DDC also increased the concentrations of ALA synthase mRNA in intestine and kidney and that testosterone elevated the concentration of the RNA in kidney. In analyses of RNA obtained from chick-embryo liver, intestine, kidney, heart, brain and lung, the probe bound primarily in each case to a single 2.3 kb RNA. Finally, the haem precursors ALA and FeCl3, when injected together into the fluid surrounding embryos, inhibited both the elevations in ALA synthase mass and RNA concentration brought about by porphyrogenic agents in liver, kidney and intestine. Thus the results indicated that: (1) certain porphyrogenic agents increased ALA synthase mass and RNA in chick-embryo intestine and kidney, in addition to liver; (2) ALA and FeCl3 inhibited the elevations; and (3) the sizes of ALA synthase's subunit as well as the enzyme's mRNA appeared identical, in each case, in all tissues examined.